2023
DOI: 10.3390/rs15235438
|View full text |Cite
|
Sign up to set email alerts
|

Forest Loss Related to Brazil Nut Production in Non-Timber Forest Product Concessions in a Micro-Watershed in the Peruvian Amazon

Gabriel Alarcon-Aguirre,
Maritza Mamani Mamani,
Rembrandt Ramiro Canahuire-Robles
et al.

Abstract: Madre de Dios is considered an important center of biodiversity in Peru due to its extensive Amazonian forests. However, the forests are under growing pressure due to land invasion, agricultural expansion, and gold mining. This makes support for forest management very important. This study aimed to evaluate the relationship between forest loss, land cover, land-use changes, and Brazil nut (Bertholletia excelsa Humb. & Bonpl) production in forest concessions in the Peruvian Amazon (2004–2020). Remote sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…AGB strongly influences ecosystem processes [79] and tropical forests store significant quantities of AGB accumulated in woody plants [86]-64% of global forest AGB [87]. However, the expansion of deforestation and forest degradation in Madre de Dios persists [19,88], resulting in the emission of carbon into the atmosphere [16]. The mean AGB determined in 20-25 years of recovery, 198 ± 115 Mg ha −1 in areas of suction pumping mining and 45 ± 78 Mg ha −1 in areas recovering from heavy machinery mining in this study is less than the mean AGB reported for tropical Amazon forest from Madre de Dios (230-450 Mg ha −1 ) [39,86,89].…”
Section: Recovery Of Agb Tree Diversity and Forest Structurementioning
confidence: 99%
“…AGB strongly influences ecosystem processes [79] and tropical forests store significant quantities of AGB accumulated in woody plants [86]-64% of global forest AGB [87]. However, the expansion of deforestation and forest degradation in Madre de Dios persists [19,88], resulting in the emission of carbon into the atmosphere [16]. The mean AGB determined in 20-25 years of recovery, 198 ± 115 Mg ha −1 in areas of suction pumping mining and 45 ± 78 Mg ha −1 in areas recovering from heavy machinery mining in this study is less than the mean AGB reported for tropical Amazon forest from Madre de Dios (230-450 Mg ha −1 ) [39,86,89].…”
Section: Recovery Of Agb Tree Diversity and Forest Structurementioning
confidence: 99%